Quality criteria of nature-based interventions in healthcare facilities: a scoping review - Sterckx, Ann; Delbaere, Ben; De Blust, Geert; Spacova, Irina; Samson, Roeland; Remmen, Roy; Keune, Hans (Frontiers in Public Health, 2024)
Introduction Implementing integrated nature-based interventions that simultaneously serve human health and the restoration of biodiversity in healthcare facilities is considered a promising strategy. As an emerging field of research and practice in healthcare, identification of quality criteria is necessary to support desired outcomes related to biodiversity, human health and intervention processes. This study is part of a larger research project in collaboration with the Flemish Agency of Nature and Forest in Belgium. Methods A scoping review was conducted in accordance with the Joanna Briggs Institute methodology for scoping reviews, in PubMed, Medline, Web of Science and Scopus. A step-by-step tabular screening process was conducted to identify relevant studies and reviews of nature-based interventions, published in English between January 2005 and April 2023. A qualitative content analysis was conducted and the results were then presented to the project steering group and a panel of stakeholders for refinement. Results After filtering on the eligibility criteria, and with focus on healthcare facilities, 14 articles were included in this study. A preliminary nature-based interventions quality framework with a set of quality indicators has been developed. Discussion When designing integrated nature-based interventions, a needs analysis of users and the outdoor environment should be conducted. Next, the integration of a One Health and biodiversity perspective and the application of a complex intervention framework, could support the quality of the design and implementation of nature-based interventions in healthcare facilities and facilitate their assessment. In future work, more rigorous research into the design and implementation of integrated nature-based interventions is needed to test and refine the quality criteria in practice.